Attributional model of visitors’ event experience in festivals and special events - Norazirah, Ayob; Nabsiah, Abd. Wahid; Azizah, Omar (The International Journal of Event Management Research, 2013)
Attribution theory is a constructive and effective application in understanding the behavioural psychology of consumers. Psychologically, individuals normally make some kind of inference from their personal analysis of behavioural facts and figures encountered on-site in order to explain an event or outcome. Subsequently, causal inferences influence individuals’ actions regardless of accuracy, quick form or biased attributions. This paper proposes an attributional model of visitors’ event experience in an attempt to search for an understanding of how people explain and account for causality of outcomes. This model provides an understanding of causal attributions of visitors’ event experience and its consequences within special event settings. According to Attribution theory, the many causal attributions may be aggregated into two dimensions (internal and external) to allow greater understanding and generalisation. Hence, it is proposed that event visitors assign causality (blame or credit) of their event experience based on event features provided by event managers as well as, external factors and social interactions with various people on-site.